BODZIEC OSTROGI Z LUB NIEWIC. SŁOWIAŃSKA KUL TURA ELITARNA W ZA CHODNIEJ CZĘŚCI PAŃSTWA PIASTÓW - Michalak, Arkadiusz; Gardeła, Leszek (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
This paper focuses on a copper-alloy goad discovered in 2017 in Lubniewice in Lubuskie Voivodeship, Poland. An interdisciplinary analysis has shown that the goad was originally part of a lavishly decorated copper-alloy spur representing a type known from high-status West Slavic graves (e.g. Lutomiersk, Ciepłe) and settlement sites. Because objects of this kind are made of costly material, and because expert skills were required to produce them, it is argued that they were commissioned by a very specific group of people who used them as “material markers” of their distinct cultural and religious identity. It is not unlikely that the owners of such spurs were members of the elite retinue of the Piasts who played important roles on and off the battlefield.